2021
DOI: 10.1039/d1cc05522d
|View full text |Cite
|
Sign up to set email alerts
|

A self-quenching fluorescence probe-mediated exponential isothermal amplification system for highly sensitive and specific detection of microRNAs

Abstract: A novel self-quenching fluorescence probe-mediated isothermal amplification system was developed, making highly sensitive and specific detection of miRNAs feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Under ideal settings, researchers in DNA biosensors have been able to rationally design intelligent IAT-based methods to quantitatively detect different targets of interest and scale-up system functionality by combining them with unique proteinases that serve as powerful ″toolboxes″ in DNA nanotechnology. For example, with DNA polymerase and nickase, Zhao et al reported a cascade amplification system for miRNA detection via the cooperation of DNA polymerization and nicking . Our group has also developed a feedback system based on three hairpin pivots and rolling circle amplification (RCA) for the determination of miRNA .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under ideal settings, researchers in DNA biosensors have been able to rationally design intelligent IAT-based methods to quantitatively detect different targets of interest and scale-up system functionality by combining them with unique proteinases that serve as powerful ″toolboxes″ in DNA nanotechnology. For example, with DNA polymerase and nickase, Zhao et al reported a cascade amplification system for miRNA detection via the cooperation of DNA polymerization and nicking . Our group has also developed a feedback system based on three hairpin pivots and rolling circle amplification (RCA) for the determination of miRNA .…”
Section: Introductionmentioning
confidence: 99%
“…For example, with DNA polymerase and nickase, Zhao et al reported a cascade amplification system for miRNA detection via the cooperation of DNA polymerization and nicking. 24 Our group has also developed a feedback system based on three hairpin pivots and rolling circle amplification (RCA) for the determination of miRNA. 9 However, these approaches still rely on the introduction of multicomponent systems consisting mostly of single-and double-stranded oligonucleotide probes, which can lead to high false-positive signals due to their susceptibility to nuclease degradation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…20,21 They are all ideal alternatives for miRNA assay. 22,23 Duplex-specic nuclease (DSN) is a special enzyme that can specically cleave double-stranded DNA or the DNA section of a DNA-RNA hybrid duplex, but it is inactive toward RNA or single-stranded DNA. [24][25][26] These characteristics endowed DSN with the ability to construct miRNA biosensors.…”
Section: Introductionmentioning
confidence: 99%